Structural Analysis and Evolution Model of the Longmaxi Formation in the Yanjin–Junlian Area of the Southern Sichuan Basin, China - Wang, Huaimin; Fan, Cunhui; Fang, Yi; Zhao, Shengxian; Shi, Xiangchao; Liu, Jianfeng; Yang, Hongfeng; Hu, Jun; Lian, Chengbo (Frontiers in Earth Science, 2022)
The Longmaxi Formation in the southern Sichuan Basin is an important target for shale gas exploration and development. The characteristics and stages of structural development significantly impact shale gas preservation and enrichment. Taking the Longmaxi Formation in the Yanjin–Junlian area of the southern Sichuan Basin as an example and based on the results of surface and underground structural analysis, fluid inclusion tests, apatite fission track experiments, and burial-thermal evolution history analysis, a comprehensive study of the development characteristics and structural stages of the Longmaxi Formation was carried out, and an evolution model was developed. (1) The Longmaxi Formation of the Yanjin–Junlian area has been affected by multistage structural movements and exhibits structural compounding and superposition corresponding to different stages. The formation of surface tracks of the folds and faults has been affected by multidirectional extrusion stresses of the near SN, NE, and near EW. There are three stages of underground faults in the Longmaxi Formation, and the strikes are nearly EW, NE, and nearly SN. (2) Three distribution intervals for the homogenization temperature ranges of fracture fillings are 161–195°C, 121–143°C, and 74–105°C. The apatite thermal history simulation reveals that the Longmaxi Formation experienced three stages of tectonic movement after its formation. (3) There were clearly three stages in the structural development of the Longmaxi Formation in this area: the late Jurassic–Palaeocene (55 ± 5–38 ± 2 Ma), Eocene–early Miocene (38 ± 2–15.5 ± 3.5 Ma), and late Miocene-present (15.5 ± 3.5 Ma–present). Thus, a compound fracture system with superimposed structural deformations in different directions and at different stages formed in the study area. (4) A model for the stages and development of structural tracks in the Longmaxi Formation was established in conjunction with structural analysis and geomechanical theory. The results have guiding significance for the evaluation of shale gas preservation conditions and accumulation in the study area.